Assessing Farmers Access to Information in Arid Western Rajasthan - KUMAR, D.; ROY, A. (Indian Journal of Hill Farming, 2015)
Agriculture in north western arid region of India is mainly rainfed. Scanty rainfall, recurrent droughts, and poor soils are characteristic of this region. Beside the agroclimatic disadvantage, the farmer of this region is resource-poor and constrained due to poor access to information on technology market and policies. The farmer is already disadvantaged because he is lacking in rainfall moreover he is lagging behind in terms of information about the sowing time, improved variety, access to information, its reliability, timeliness and cost effectiveness. The present study was conducted with the objective to assess farmer’s access to information and assessing its timeliness, cost effectiveness and reliability of the information to farmers using primary data collected from randomly selected 30 farmers each from Jodhpur and Jhunjhunu district of arid western Rajasthan. It was observed that farmer is not getting timely, reliable and cost effective information. Majority of the farmers hardly have any access to reliable information. Major sources of information were private input dealers and fellow farmers.